GE_GERICHTE P/24474/2014 vom 31. März 2016 - GE Cour de justice (2016)
AGRESSION; LÉSION CORPORELLE; BAGARRE; DANCING; TÉMOIN; ASSISTANCE JUDICIAIRE; DÉNUEMENT; AIDE AUX VICTIMES; HONORAIRES; AVOCAT; ABUS DE DROIT | CPP.310; CP.134; CP.123; CPP.136; LAVI.7; LAVI.30